Combined application of biochar and sulfur alleviates cadmium toxicity in rice by affecting root gene expression and iron plaque accumulation - Sun, Xiaoxue; Wang, Jiangnan; Zhang, Miao; Liu, Zunqi; E, Yang; Meng, Jun; He, Tianyi (Ecotoxicology and environmental safety, 2023)
Biochar and sulfur are considered useful amendments for soil cadmium (Cd) contamination remediation. However, there is still a gap in the understanding of how combined biochar and sulfur application affects Cd resistance in rice, and the role of the accumulation of iron plaque and the expression of Cd efflux transporter-related genes are still unclear in this type of treatment. In this study, we screened an effective combination of biochar and sulfur (0.75 % biochar, 60 mg/kg sulfur) that significantly reduced the Cd content of rice roots (32.9 %) and shoots (12.3 %); significantly reduced the accumulation of amino acids and their derivatives, organic acids and their derivatives and flavonoids in rice roots; and altered secondary metabolite production and release. This combined biochar and sulfur application alleviated the toxicity of Cd to rice, in which the enhancement of iron plaque (24.8 %) formation and upregulated expression of heavy metal effector genes (NRAMP3, MTP3, ZIP1) were important factors. These findings show that iron plaque and heavy metal transport genes are involved in the detoxification of rice under the combined application of biochar and sulfur, which provides useful information for the combined treatment of soil Cd pollution. [Display omitted] •Combined application of biochar and sulfur can significantly reduce the accumulation of Cd all parts of the rice plant.•Increased iron plaque accumulation is an important factor in the combined application decreasing the uptake of Cd in rice.•The combined application of biochar and sulfur reduces the stress response of rice under Cd stress.•Combined biochar and sulfur application significantly upregulates the expression of genes encoding efflux proteins.